Titanium alloys: in vitro biological analyzes on biofilm formation, biocompatibility, cell differentiation to induce bone formation, and immunological response - Mello, Daphne de Camargo Reis [UNESP]; de Oliveira, Jonatas Rafael [UNESP]; Cairo, Carlos Alberto Alves; Ramos, Lais Siebra de Brito [UNESP]; Vegian, Mariana Raquel da Cruz [UNESP]; de Vasconcellos, Luis Gustavo Oliveira [UNESP]; de Oliveira, Felipe Eduardo; de Oliveira, Luciane Dias [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP] (My University, 2019)
Biological effects of titanium (Ti) alloys were analyzed on biofilms of Candida albicans, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus mutans, and Streptococcus sanguinis, as well as on osteoblast-like cells (MG63) and murine macrophages (RAW 264.7). Standard samples composed of aluminum and vanadium (Ti-6Al-4V), and sample containing niobium (Ti-35Nb) and zirconium (Ti-13Nb-13Zr) were analyzed. Monomicrobial biofilms were formed on the Ti alloys. MG63 cells were grown with the alloys and the biocompatibility (MTT), total protein (TP) level, alkaline phosphatase (ALP) activity, and mineralization nodules (MN) formation were verified. Levels of interleukins (IL-1β and IL-17), tumor necrosis factor alpha (TNF-α), and oxide nitric (NO) were checked, from RAW 264.7 cells supernatants. Data were statically analyzed by one-way analysis of variance (ANOVA) and Tukey’s test, or T-test (P ≤ 0.05). Concerning the biofilm formation, Ti-13Nb-13Zr alloy showed the best inhibitory effect on E. faecalis, P. aeruginosa, and S. aureus. And, it also acted similarly to the Ti-6Al-4V alloy on C. albicans and Streptococcus spp. Both alloys were biocompatible and similar to the Ti-6Al-4V alloy. Additionally, Ti-13Nb-13Zr alloy was more effective for cell differentiation, as observed in the assays of ALP and MN. Regarding the stimulation for release of IL-1β and TNF-α, Ti-35Nb and Ti-13Nb-13Zr alloys inhibited similarly the synthesis of these molecules. However, both alloys stimulated the production of IL-17. Additionally, all Ti alloys showed the same effect for NO generation. Thus, Ti-13Nb-13Zr alloy was the most effective for inhibition of biofilm formation, cell differentiation, and stimulation for release of immune mediators. [Figure not available: see fulltext.].